The Relationship Between Family Support and Motivation to Recover in Clients at the Ar-Rahman Drug Rehabilitation Center Foundation, Palembang - Irawati Adhal Laeli; Mirna Ari Mulyani; Bela Janare Putra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study is entitled The Relationship of Family Support with Motivation to Recover to Clients at the Ar -Rahman Palembang Narcotics Rehabilitation Center Foundation. The purpose of this study was to determine the relationship of family support with motivation to recover on clients at the Ar-Rahman Palembang Narcotics Rehabilitation Center Foundation. The method in this researcher is quantitative with the type of correlational research. The sample of this study totaled 45 respondents and sampling techniques in the form of purposive sampling. This study uses a prerequisite test consisting of a normality test, linearity and hypothesis test using SPSS assistance. Data collection methods using a questionnaire. The results show that the client rehabilitation has a moderate level of family support (69%) and the level of motivation to recover is moderate (65%). By using the Pearson Product Moment correlation, researchers found that the Rxy value = 0.303 with a significant 0.043 P = 0.043 (p <0.05). This means there is a positive relationship between family support and motivation to recover on clients at the Ar-Rahman Palembang drug rehabilitation center foundation. The relationship shows that the higher the family support, the higher the motivation to recover, the lower the family support, the lower the motivation to recover.